A New Approach to Measuring the Temperature of Fluids Reaching 300 ℃ and 2 mol/kg NaCl Based on the Raman Shift of Water. Issue 11 (November 2018) - Li, Lianfu; Zhang, Xin; Luan, Zhendong; Du, Zengfeng; Xi, Shichuan; Wang, Bing; Lian, Chao; Yan, Jun
The OH stretching band of water is very sensitive to temperature and salinity for the existence of hydrogen bonds between H2 O molecules. In this study, the OH stretching band was deconvoluted into two Gaussian peaks, with peak 1 at approximately 3450 cm −1 and peak 2 at approximately 3200 cm −1 . The positions of peaks 1 and 2 both shifted to higher wavenumbers with increasing temperature from 50 ℃ to 300 ℃. The effects of salinity in the range of 0–2 mol/kg NaCl on the OH stretching band were also studied. Linearity for the relationship between Raman shift of peak 1 and temperature increased as the salt concentration increased from 0 to 2 mol/kg, while peak 2 displayed an opposing trend. Two temperature calibration models were developed based on the temperature-dependent changes in the Raman frequency shifts of peaks 1 and 2 (precision of 0.9 ℃ and 1.0 ℃, respectively). The calibration models for temperature were successfully applied to determining the temperatures of deep-sea hydrothermal fluids in the Okinawa Trough hydrothermal field. The degree of mixing of hydrothermal fluids and ambient seawater during in situ Raman measurements was estimated by the difference in temperatures determined through these calibration models and those measured through thermocouple sensors.